Enhancing Service Quality Through Good Governance Practice in Zakat Institution - Norsyella Ahmad Tamizi; Umi Hamidaton Mohd Soffian Lee; Nor Azima Ahmad; Muhammad Hakimi Mohd Shafiai (Human Resource Management Academic Research Society, 2024)
Indexed by ERA